Alveolodental trauma of the maxillary permanent incisors at Bouaké University Hospital (Côte d'Ivoire) - Eric Kouassi Zegbeh-N'guessan; Ernest Martial Djémi; Pornan Issa Jules Bérété; Diane Affoué Ba Amenou; Demisères Alexandre Ory (Elsevier, 2024)
Introduction: dental trauma, particularly to the maxillary permanent incisors, is relatively common at Bouaké University Hospital. The aim was to identify the epidemioclinical characteristics and distinguish the therapeutic methods. Material and methods: This was a retrospective cross-sectional study carried out in the Odontostomatology and Maxillofacial Surgery Department of Bouaké University Hospital from 2015 to 2021. Alveolar-dental trauma of the maxillary permanent incisors was included in the study. Results: 346 subjects were enrolled, representing a prevalence of 20.99 % of all maxillofacial injuries. The mean age was 23.5 years (extremes 8 and 73 years) and the sex ratio was 3.55. Road traffic accidents were the cause of trauma in 250 cases (72.25 %), of which 213 (85.20 %) involved motorised 2-wheelers without helmets. Concurrent damage to the central and lateral incisors was observed in 178 cases (51.44 %). The dental organ was affected in 219 cases (63.29 %), the supporting tissue in 183 cases (52.89 %) and the bone tissue in 102 cases (29.48 %). Other associated craniofacial lesions were observed in 135 cases (39.02 %). For lesions of the dental support tissue, reduction and retention were performed in 39 cases (21.31 %). For lesions of the dental organ, dental avulsion was performed in 102 cases (46.58 %). For alveolar bone lesions, For alveolar bone lesions, reduction with maxillo-mandibular blocking was performed in 54 cases (52.94 %). Discussion: Alveolodental traumatic lesions of the maxillary permanent incisors are, in more than a third of cases, included in a multi-traumatic maxillofacial context, and can therefore very easily be relegated to secondary consideration. Conclusion: These traumas most often affect young patients, with major lesions that need to be treated as effectively as possible, at the risk of significant functional and aesthetic sequelae.